Effects of impaired membrane interactions on α-synuclein aggregation and neurotoxicity - Ysselstein, Daniel (Neurobiol Dis, 2015)
The post-mortem brains of individuals with Parkinson’s disease (PD) and other synucleinopathy disorders are characterized by the presence of aggregated forms of the presynaptic protein α-synuclein (aSyn). Understanding the molecular mechanism of aSyn aggregation is essential for the development of neuroprotective strategies to treat these diseases. In this study, we examined how interactions between aSyn and phospholipid vesicles influence the protein’s aggregation and toxicity to dopaminergic neurons. Two-dimensional NMR data revealed that two familial aSyn mutants, A30P and G51D, populated an exposed, membrane-bound conformer in which the central hydrophobic region was dissociated from the bilayer to a greater extent than in the case of wild-type aSyn. A30P and G51D had a greater propensity to undergo membrane-induced aggregation and elicited greater toxicity to primary dopaminergic neurons compared to the wild-type protein. In contrast, the non-familial aSyn mutant A29E exhibited a weak propensity to aggregate in the presence of phospholipid vesicles or to elicit neurotoxicity, despite adopting a relatively exposed membrane-bound conformation. Our findings suggest that the aggregation of exposed, membrane-bound aSyn conformers plays a key role in the protein’s neurotoxicity in PD and other synucleinopathy disorders.